Facial Wound by a Steel Blade. A Case Presentation. - Orlando Jesús Sotolongo Terry; Ángel Luis Cruz Leiva; Leonardo Atienza Lois (Medisur)
A 15 year-old half-breed man who lives in the rural area came to the emergence ward of the National Hospital in Timor with an arrow inserted in the third half of his face. Due to this a surgical treatment was applied. Our objective when presenting this case is to show the importance of multifactorial treatment carried out in patients with this kind of traumatism which could have engaged his life.